Medication Errors and Type 2 Diabetes Management: A Qualitative Exploration of Physicians' Perceptions, Experiences and Expectations From Quetta City, Pakistan - Habib, Muhammad Kashif; Khan, Muhammad Naeem; Sadiq, Abdul; Iqbal, Qaiser; Raziq, Abdul; Ahmad, Nafees; Iqbal, Zaffar; Haider, Sajjad; Anwar, Muhammad; Khilji, Fazal ur Rehman; Saleem, Fahad; Khan, Amer Hayat (Frontiers in Medicine, 2022)
Background: Type 2 Diabetes-related medication errors are frequently reported from the hospitals and consequently are of major concern. However, such reports are insufficient when developing healthcare settings are pursued in literature. Keeping this inadequacy in mind, we therefore aimed to explore physicians’ perceptions, experiences and expectations of medication errors when managing patients with Type 2 Diabetes Mellitus. Methods: A qualitative design was adopted. By using a semi-structured interview guide through the phenomenology-based approach, in-depth, face-to-face interviews were conducted. Physicians practicing at the medicine ward of Sandeman Provincial Hospital, Quetta, were purposively approached for the study. All interviews were audio-taped, transcribed verbatim, and were then analyzed for thematic contents by the standard content analysis framework. Results: Although the saturation was reached at the 13th interview, we conducted additional two interviews to ensure the saturation. Fifteen physicians were interviewed, and thematic content analysis revealed six themes and nine subthemes. Mixed conceptualization and characterization of medication errors were identified. Medication errors were encountered by all physicians however poor understanding of the system, deficiency of logistics and materials were rated as barriers in reporting medication errors. Among contributors of medication errors, physicians themselves as well as dispensing and patient-related factors were identified. Physicians suggested targeted training sessions on medication error-related guidelines and reporting system. Parallel, establishment of an independent unit, involving the pharmacists, and strict supervision of paramedics to minimize medication errors was also acknowledged during data analysis. Conclusion: With a longer life expectancy and a trend of growing population, the incidences of medication errors are also expected to increase. Our study highlighted prescribing, dispensing and administration phases as contributing factors of medication errors. Although, physicians had poor understanding of medication errors and reporting system, they believed getting insights on guidelines and reporting system is essential. A review of admission and discharge reconciliation must be prioritized and a culture of teamwork, communication and learning from mistakes is needed.